Pendidikan dan Masa Depan: Tingkat Kesadaran Masyarakat Tentang Pendidikan di Kelurahan Rahma - Nurlila Kamsi; Mita Safitri; Roybah Roybah (Edification Journal : Pendidikan Agama Islam, 2021)
This study aims to describe the development of education in Lubuklinggau City, especially Rahmah Village. To describe the factors that cause the lack of awareness of the Rahmah village community about education. This research use desciptive qualitative approach. In obtaining the data, the writer uses observation, interview, and documentation techniques. From the results of this study, it was found that: education in Rahmah Village has progressed where several educational institutions such as PAUD, TK, and SD. The education in the Rahmah Village is quite good but there is still little public awareness about education where only those who receive education up to basic education are still few at the top level. There are several factors that cause a lack of public awareness of higher education such as: economy, work, lack of family attention, and being influenced by relationships.